Stability-indicating RP-LC method for quantification of fusidic acid in cream - Curbete, Mariane Machado [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (FapUNIFESP (SciELO), 2016)
Fusidic acid is an antibiotic steroid indicated for the treatment of infections caused by the genus Staphylococcus, including methicillin resistant Staphylococcus aureus strains, and other Gram-positive bacteria. In the present study, a stability-indicating reversed-phase liquid chromatography (RP-LC) method was developed and validated for the determination of fusidic acid in dermatological cream as an alternative to existing methods. Analyses were performed using a C18 column and guard column at room temperature, eluting with an isocratic mobile phase of acetonitrile and water (72: 28, v/v), adjusted to pH 3.5 with acetic acid, pumped at a flow rate of 1.0 mL min-1, detection at 210 nm and 20 µL of injection volume. The forced degradation study was conducted under acidic, alkaline, neutral, photolytic, and oxidative stress conditions. The method was validated according to ICH and FDA guidelines; it was linear, precise, accurate, selective, and robust over concentrations of 5-95 µg mL-1, with detection and quantification limits of 0.43 and 1.31 µg mL-1, respectively. Therefore, we conclude that this method is suitable for quantifying fusidic acid in pharmaceutical dermatological creams and determining its stability, representing a more economical and practical alternative for routine analysis in quality control.
Keywords: Chromatography/reversed-phase; Fusidic acid/stability-indicating/quality control/validation